MINICUENTOS - Rojas Ballesteros, Paola Andrea; Arteaga, Carlos Eduardo; Peña Morales, Yenny Johana; Ramirez, Magda Biviana (Revista Entrelíneas, 2019)
Un Angel Los tres primos bambú Un Principe inoportuno Juego de NIños